English for Business / The Ideal Study Companion - Whitehead David; Whitehead Geoffrey (Made Simple Books, 1993)
Every book in this series is designed to help you get the grips with a complex subject. They explain the basics first, using straightforward language, and gradually introduce you to more advanced topics. Preface, Acknowledgements, How to Use this Book, An Introduction to Business English, The Parts of Speech, Reading for Business Purposes, Writing Business Letters, Some Special Types of Letter, Writing in Paragraphs, Face-to-Face Communication, Communication about Marketing, English and Business Meetings, Writing a Summary, The Tenses of Verbs, The Use of the Dictionary, Report Writing 1: Gathering Information, Report Writing 2: The Body of the Report, Correspondence about Employment, Conferences and Functions, Technical Aids to Business Communication, Appendix: Professional Bodies, Index.